2019
DOI: 10.2987/19-6858.1
|View full text |Cite
|
Sign up to set email alerts
|

From Surveillance To Control: Evaluation of A Larvicide Intervention Against Aedes aegypti In Brownsville, Texas

Abstract: South Texas is recognized as a potential area for the emergence and re-emergence of mosquitoborne diseases due to recent circulation of Zika, chikungunya, and dengue viruses. During 2017, high Aedes aegypti abundance found in the city of Brownsville, TX, in combination with the previous year's local transmission of Zika virus, triggered the activation of the Texas Department of State Health Services Emergency Mosquito Control Contingency Contract. A contract with the Clarke Environmental and Mosquito Control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…11 In comparison with another study using vehicle-mounted equipment where the net level of control reported was a 29% reduction of Ae. aegypti in treatment sites, 14 the study in Bayamón showed some improvement of the technique, with 28% and 62% reductions in numbers of Ae. aegypti in treatment sites compared with the control.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…11 In comparison with another study using vehicle-mounted equipment where the net level of control reported was a 29% reduction of Ae. aegypti in treatment sites, 14 the study in Bayamón showed some improvement of the technique, with 28% and 62% reductions in numbers of Ae. aegypti in treatment sites compared with the control.…”
Section: Resultsmentioning
confidence: 96%
“…WALS® application of Bti AM65‐52 WDG has been successful for dengue vector and disease suppression in Malaysia 10, 11 and in Key West, Florida 12 . WALS® was also used successfully in Miami, Florida 13 and Brownsville, Texas 14 during the Zika crisis of 2016. Therefore, in an effort to find a solution that can be applied to entire communities at speed and at scale, a trial was launched in Puerto Rico to test the effectiveness of applying Bacillus thuringiensis israelensis ( Bti ) AM65‐52 WDG (VectoBac® WDG, Valent Biosciences LLC) using vehicle‐mounted WALS® across multiple areas in the island's urban environments to control Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AGO has been shown as an efficient surveillance and control tool in Puerto Rico and has reduced chikungunya virus incidence in humans (Sharp et al, 2019). Before wide implementation of this tool by vector control programmes in other regions, its evaluation based on community acceptance, field operational performance and overall efficiency for both surveillance and control, needs to be assessed under different local settings (Garcia-Luna et al, 2019;Gunning et al, 2018;Lenhart et al, 2020). The AGO has been shown to be a cost-effective tool for the surveillance of adult A. aegypti in both San Antonio (Obregón et al, 2019) and the Lower Rio Grande Valley (LRGV) region (Martin et al, 2019) in South Texas.…”
Section: Introductionmentioning
confidence: 99%
“…In the Lower Rio Grande Valley (LRGV) of South Texas, we completed several studies on Ae. aegypti to better understand ecological and social aspects of this mosquito vector [ 4 , 5 ] and to evaluate control tools under local settings [ 6 ]. Our research team will conduct an intervention study of Ae.…”
Section: Introductionmentioning
confidence: 99%